TEACHER COMPETENCE IN THE BOOK OF TARBIYATUL AWLAD FII ISLAM BY ABDULLAH NASHIH ULWAN - Arsyad, Junaidi; Hanum OK, Azizah; Pasaribu, Taupik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
This study aims to: 1) Analyze teacher competence according to Abdullah Nashih Ulwan's perspective. 2) Analyzing the contribution of Abdullah Nashih Ulwan's thoughts on education and its relevance to Islamic education in Indonesia. This research is qualitative research that produces descriptive data To examine the problems that have been formulated, literature studies are used. Research data sources are grouped into (1) primary data sources are the original works of Abdullah Nashih Ulwan, and (2) secondary data sources are written documents in the form of books and journals that discuss Abdullah Nashih Ulwan's thoughts. The results showed that: 1) The competencies that must be possessed by a teacher from the perspective of Abdullah Nashih Ulwan are sincerity, taqwa, knowledge, polite forgiving, and awareness of responsibility. Through these competencies, a teacher is expected to be an educator who can develop the potential of students 2) The book of Tarbiyatul Awlad Fil Islam itself has a contribution to Islamic education, namely Abdullah Nashih Ulwan offers a method of moral education for children in the family, including: 1. Education by example, 2. Education by custom, 3. Education by advice, 4. Education by attention, 5. Education by giving punishment